INTEGRALIDADE NO PROCESSO DE CUIDAR DE PESSOAS COM DIABETES MELLITUS EM UM CENTRO DE SAÚDE DE FEIRA DE SANTANA BA. - Bastos, Leonor da Silva (2008)
Care has always been part of human life. It is associated to the practice of the women who have thereby, in the everyday life and surrounded by cultural connotations, promoted life in all its forms and taken care of death. Because life is complex and multi-faceted, this care, in order to fulfill its role of protecting and defending life, needs to be drawn from multiple perspectives and wisdoms, in an articulated manner and in multiple technological levels, including the lighter ones. As such, it depends on the enlivened work of an integrated health team. This team should perform careful and constant action involving workers, user, family and community, and be based on social bonds and accountability. Care, as a result of this collective action integrating distinct perspectives and wisdoms, is nowadays the axis of all actions in health service, particularly in Basic Healthcare Units, which are usually the door to the healthcare needs of the local population. This study adopts such a perspective, and examines the process of care of persons with diabetes mellitus (DM) in a Healthcare Center of Feira de Santana. Its objective is to analyze the process of care of persons with DM aiming for the integrality of healthcare attention, and to discuss its guiding devices: access, bond-accountability, team-formation (the construction of subjects, insertion and habilitation), in the everyday dynamics of the Healthcare Unit. The methodology is qualitative and used semi-structured interviews and systematic observations as data collection techniques. As subjects, the study took healthcare workers and users enrolled in the Program of Attention to persons with DM. The method of analysis for the interviews was guided by the Thematic Subject Analysis (MINAYO, 1996) and the Analyzer Flowchart of Merhy (1997), which also grounded the analysis of the observations. The results reveal that the process of caring of persons with DM has as its main intervention core the practice of nursing (in particular that of the nurse). In the everyday context of the healthcare services, that process has been fragmented, disconnected, and guided by the doctor-centered model. Access is limited, focused, and oriented towards low-complexity actions. Bond and user-embracement are still performed distanced from co-accountability (workers, users, service networks) in the definition of the therapeutic project of the persons with DM and who need the Healthcare Unit. In conclusion, the study points as necessary an expansion of the debate on integral care, considering the everyday praxis of those involved in the process. Key-words: Care has always been part of human life. It is associated to the practice of the women who have thereby, in the everyday life and surrounded by cultural connotations, promoted life in all its forms and taken care of death. Because life is complex and multi-faceted, this care, in order to fulfill its role of protecting and defending life, needs to be drawn from multiple perspectives and wisdoms, in an articulated manner and in multiple technological levels, including the lighter ones. As such, it depends on the enlivened work of an integrated health team. This team should perform careful and constant action involving workers, user, family and community, and be based on social bonds and accountability. Care, as a result of this collective action integrating distinct perspectives and wisdoms, is nowadays the axis of all actions in health service, particularly in Basic Healthcare Units, which are usually the door to the healthcare needs of the local population. This study adopts such a perspective, and examines the process of care of persons with diabetes mellitus (DM) in a Healthcare Center of Feira de Santana. Its objective is to analyze the process of care of persons with DM aiming for the integrality of healthcare attention, and to discuss its guiding devices: access, bond-accountability, team-formation (the construction of subjects, insertion and habilitation), in the everyday dynamics of the Healthcare Unit. The methodology is qualitative and used semi-structured interviews and systematic observations as data collection techniques. As subjects, the study took healthcare workers and users enrolled in the Program of Attention to persons with DM. The method of analysis for the interviews was guided by the Thematic Subject Analysis (MINAYO, 1996) and the Analyzer Flowchart of Merhy (1997), which also grounded the analysis of the observations. The results reveal that the process of caring of persons with DM has as its main intervention core the practice of nursing (in particular that of the nurse). In the everyday context of the healthcare services, that process has been fragmented, disconnected, and guided by the doctor-centered model. Access is limited, focused, and oriented towards low-complexity actions. Bond and user-embracement are still performed distanced from co-accountability (workers, users, service networks) in the definition of the therapeutic project of the persons with DM and who need the Healthcare Unit. In conclusion, the study points as necessary an expansion of the debate on integral care, considering the everyday praxis of those involved in the process.